2020
DOI: 10.7717/peerj.9633
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 10 Hub genes related to the progression of colorectal cancer by co-expression analysis

Abstract: Background Colorectal cancer (CRC) is the third most common cancer in the world. The present study is aimed at identifying hub genes associated with the progression of CRC. Method The data of the patients with CRC were obtained from the Gene Expression Omnibus (GEO) database and assessed by weighted gene co-expression network analysis (WGCNA), Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses performed in R by WGCNA, several hub genes that regulate the mechanism of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(34 reference statements)
3
8
0
Order By: Relevance
“…These findings were verified in 65 pairs of cancer and adjacent tissues in patients with CRC. These results were consistent with those reported by Meng et al [ 16 ] and Arriaga et al [ 13 ]. However, other studies have shown that MT2A is upregulated in human colorectal adenocarcinoma HT29 cells [ 12 ], and the interaction between pFADD and MT2A inhibits the apoptosis of Colo 205 cells and induces cell proliferation [ 14 ].…”
Section: Resultssupporting
confidence: 94%
“…These findings were verified in 65 pairs of cancer and adjacent tissues in patients with CRC. These results were consistent with those reported by Meng et al [ 16 ] and Arriaga et al [ 13 ]. However, other studies have shown that MT2A is upregulated in human colorectal adenocarcinoma HT29 cells [ 12 ], and the interaction between pFADD and MT2A inhibits the apoptosis of Colo 205 cells and induces cell proliferation [ 14 ].…”
Section: Resultssupporting
confidence: 94%
“…For example, in the work of Baier et al [18] it was proved that the concentration in cancer tissue is signi cantly higher compared to normal tissue. Similar results were also obtained by other researchers such as Hu et al [19], Yu et al [20], Meng et al [21], Rubie et al [22] and Zhang et al [23]. In the case of two last of mentioned studies, the authors additionally performed an analysis of gene expression (qRT-PCR), which, along with similar results obtained in the work of Novillo et al [24], con rmed the increase of CXCL5 in the course of CRC.…”
Section: Discussionsupporting
confidence: 85%
“…Meng and colleagues applied WGCNA to identify hub genes in the progression of colorectal cancer [42]. They reported IL10RA as one of hub genes with a lower mRNA expression in colorectal cancer samples compared to normal.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the biomarkers were validated by real-time quantitative PCR analysis. A recent study applied WGCNA on colorectal cancer samples obtained from two GEO datasets [42]. The nodes with higher degrees in the network were identified as hub genes after mapping of differentially expressed genes found in important modules over the STRING network.…”
Section: Introductionmentioning
confidence: 99%